Association between integration structure and functional evolution in the opercular four‐bar apparatus of the threespine stickleback, Gasterosteus aculeatus (Pisces: Gasterosteidae). (22nd November 2013) - Jamniczky, Heather A.; Harper, Emily E.; Garner, Rebecca; Cresko, William A.; Wainwright, Peter C.; Hallgrímsson, Benedikt; Kimmel, Charles B.
<x xml:space="preserve">Abstract</x> Phenotypes may evolve to become integrated in response to functional demands. Once evolved, integrated phenotypes, often modular, can also influence the trajectory of subsequent responses to selection. Clearly, connecting modularity and functionally adaptive evolution has been challenging. The teleost skull and jaw structures are useful for understanding this connection because of the key roles that these structures play in feeding in novel environments with different prey resources. In the present study, we examined such a structure in the threespine stickleback: the opercular four‐bar lever that functions in jaw opening. Comparing oceanic and two fresh‐water populations, we find marked phenotypic divergence in the skull opercular region, and the major axes of morphological and functional variation of the lever are found to be highly correlated. All three populations share the same global skull integration structure, and a conserved, strongly‐supported modular organization is evident in the region encompassing the lever. Importantly, a boundary between two modules that subdivides the lever apparatus corresponds to the region of most prominent morphological evolution. The matched modular phenotypic and functional architecture of head and jaw structures of stickleback therefore may be important for facilitating their rapid adaptive transitions between highly divergent habitats. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 111, 375–390.